Operative and Oncological Outcomes Comparing Sentinel Node Mapping and Systematic Lymphadenectomy in Endometrial Cancer Staging: Meta-Analysis With Trial Sequential Analysis - Gu, Yu; Cheng, Hongyan; Zong, Liju; Kong, Yujia; Xiang, Yang (Frontiers in Oncology, 2021)
Objective To evaluate the utility of sentinel lymph node mapping (SLN) in endometrial cancer (EC) patients in comparison with lymphadenectomy (LND). Methods Comprehensive search was performed in MEDLINE, EMBASE, CENTRAL, OVID, Web of science databases, and three clinical trials registration websites, from the database inception to September 2020. The primary outcomes covered operative outcomes, nodal assessment, and oncological outcomes. Software Revman 5.3 was used. Trial sequential analysis (TSA) and Grading of Recommendations Assessment, Development, and Evaluation (GRADE) were performed. Results Overall, 5,820 EC patients from 15 studies were pooled in the meta-analysis: SLN group (N = 2,152, 37.0%), LND group (N = 3,668, 63.0%). In meta-analysis of blood loss, SLN offered advantage over LND in reducing operation bleeding (I2 = 74%, P<0.01). Z-curve of blood loss crossed trial sequential monitoring boundaries though did not reach TSA sample size. There was no difference between SLN and LND in intra-operative complications (I2 = 7%, P = 0.12). SLN was superior to LND in detecting positive pelvic nodes (P-LN) (I2 = 36%, P<0.001), even in high risk patients (I2 = 36%, P = 0.001). While no difference was observed in detection of positive para-aortic nodes (PA-LN) (I2 = 47%, P = 0.76), even in high risk patients (I2 = 62%, P = 0.34). Analysis showed no difference between two groups in the number of resected pelvic nodes (I2 = 99%, P = 0.26). SLN was not associated with a statistically significant overall survival (I2 = 79%, P = 0.94). There was no difference in progression-free survival between SLN and LND (I2 = 52%, P = 0.31). No difference was observed in recurrence. Based on the GRADE assessment, we considered the quality of current evidence to be moderate for P-LN biopsy, low for items like blood loss, PA-LN positive. Conclusion The present meta-analysis underlines that SLN is capable of reducing blood loss during operation in regardless of surgical approach with firm evidence from TSA. SLN mapping is more targeted for less node dissection and more detection of positive lymph nodes even in high risk patients with conclusive evidence from TSA. Utility of SLN yields no survival detriment in EC patients.